Pengaruh Lama Fermentasi terhadap Karakteristik Minuman Probiotik Sari Buah Mangga Arumanis (Mangifera indica L. Var Arumanis) dengan Lactobacillus rhamnosus SKG 34 - Ardiani, Ni Wayan Dewi; Nocianitri, Komang Ayu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Mango fruit is a local fruit with the third highest production level in Indonesia, one of the varieties is Arumanis mango. The increase in production during the season causes the market price of mangoes to be low, besides that arumanis mangoes have a short shelf life and have perishable properties, so processing is needed to increase economic value and maintain its shelf life by doing diversification into probiotic drinks. Fermentation time is an important factor in the growth of probiotic bacteria and affects product characteristics. This study aims to determine the effect of fermentation time on the characteristics of arumanis mango probiotic drink with Lactobacillus rhamnosus SKG34 and to determine how much fermentation time to produce arumanis mango probiotic drink with the best characteristics. This study used a Completely Randomized Design (CRD) with fermentation time as treatment factor, namely 0 hours, 6 hours, 12 hours, 18 hours, 24 hours, and 30 hours. Each treatment was repeated 3 times to obtain 18 experimental units. The data were analyzed by Analysis of Variance and if the treatment had a significant effect, then continued with the Duncan Multiple Range Test. The results showed that fermentation time had a significant effect on total LAB, total acid, pH, total sugar, hedonic of taste, sour taste score, sweet taste score and overall acceptance, but had no significant effect on hedonic of color and aroma. Fermentation for 18 hours produced of arumanis mango juice probiotic drink with the best characteristics, with total LAB of 10.28 Log CFU/ml, total acid 0.22 percent, total sugar 12.70 percent, pH 4.28, color, taste, overall acceptance is preferred, with the criteria of slightly sour and slightly sweet taste, and slightly preferred of aroma.